(untitled) (Journal of Economic Research & Business Administration, 2016)
The financial condition of the company’s financial position shows its economic activity, the ability to repay its debt obligations in time within a certain period for uninterrupted provision of financial resources. Finan cial sustainability – this relationship of equity and debt. The company is considered to be financially sustainable, if income exceeds expenditure. Financial sustainability characterizes a condition of the financial resources that enable effective use of funds for the continuity of the process of pro duction and sales, as well as the modernization and expansion of the com pany. Analysis and evaluation of efficiency of the business activities of the company is the final stage of the financial analysis. Payments of dividends the company’s shares is the main source of revenue, and an increase in the market value of the shares in the future attract investors. The article con cider the coefficients defining financial stability and correlation the stock price to earnings per share as the market appeal of the company.